(untitled) (Al-Qamar, 2021)
Islam gives mankind a complete and comprehensive system of life and it demands from its followers to follow Islam is all fields of life. “Islamic requirements of ادخلو فی السلم کآفۃ, contemporary situation and its realization” is a topic which demands to follow Islam in all the parts of life. The main focus of this topic is how far the Muslim Ummah have gone away from teachings of Islam and in present age how blindly following their own psychological desires and western culture. Islam gives importance to human wisdom but not before the orders of Allah Subhanahu Wa Ta’ala because this wisdom and reason if it tries to figure out “Wahi e Ilahi” will cause mis-guidance and dis-obedience. Muslim Ummah should refrain from discriminating and finding faults against the guided group of Sahaba Ikram and follow them. Muslims are arrogant and rebellious in their worship and affaires. Islam is a religion in which collective welfare is given priority over personal benefits but it gives a system which is a balanced combination of individuality and collectively. This research paper examines the behavior of contemporary Muslims as opposed to the Islamic requirements for full access to Islam and addresses this issue in the light of Islami Teachings to Muslim Ummah to follow the patterns of ادخلو فی السلم کآفۃ.